Self efficacy, self esteem and intrinsic motivation to learn: a perspective of Malaysian business students / Norashikin Hussein …[et al.] - Mohd Fauzi, Muna Wadhiha; Aluwi, Ainie Hairianie; Ahmad Zayadah, Mazlina; Hussein, Norashikin (Universiti Teknologi MARA, 2021)
Intrinsic motivation is driven by internal rewards that are satisfying to the individuals. In the context of learning, intrinsic motivation is imperative as the outcome of the learning process was found to be more sustainable and high quality. Since intrinsic motivation comes from within individual, thus it is interesting to explore self-concept variables that lead to intrinsic motivation. Thus, the aims of the study are firstly, to determine the relationship between self- efficacy and intrinsic motivation to learn; secondly, to determine the relationship between self-efficacy and intrinsic motivation to learn. Data were collected using questionnaire survey to 200 bachelor degree program students in a public university in Malaysia. Data were then analyzed using SPSS Statistics. Findings of the study indicate that out of the two independent variables, only self-efficacy was found to influence intrinsic motivation to learn among students. This study is imperative to the educators and higher learning institutions in identifying self-concepts variables that are significant in motivating students intrinsically. This study also provides insights in designing relevant policies, programs and workshops for the students in increasing self-efficacy among students.